Identifying palliative home care needs of patients with advanced cancer: a cross-sectional study - Liu, Xiaocheng; Liu, Hui; Ying, Wenjuan; Zhang, Yuying; Gong, Xiaoling; Huang, Junfang (Frontiers in Psychiatry, 2025)
BackgroundHome-based palliative care is an ideal model for providing continuous, effective, and timely care at the patient’s home. However, the timely recognition of palliative home care needs remains a clinical challenge, and few studies have described the characteristics of palliative care needs and quality of life at home.ObjectivesTo identify the palliative home care needs of patients with advanced cancer and explore the influencing factors in addressing these needs.MethodsIn this cross-sectional study, convenience samples were collected from four cities in mainland China between May 2020 and November 2021. The revised Problems and Needs in Palliative Care-short version was used to evaluate palliative home care needs. The European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-C30 was used to evaluate the participants’ quality of life. We used SPSS version 23.0 for all statistical analyses. Descriptive statistics, Wilcoxon rank sum test, Spearman rho correlation independent t-test, and multiple linear regression were performed to analyze the data.ResultsCompleted the survey. The patients’ palliative home care needs were primarily related to physical symptoms, home health care services, and psychological issues. For items, the top three palliative home care needs were related to financial needs, “extra expenditures because of the disease” (75.9%), psychological issues, “fear of getting worse” (72.8%), and “fear of physical suffering” (67.9%). Multiple linear regression analysis revealed that 53.5% of palliative home care needs could be explained by the Karnofsky Performance Status and quality of life: physical, role, emotional, and financial difficulties dimensions.ConclusionThe palliative home care needs were associated with patients’ quality of life and financial difficulties. These findings may contribute to provide a framework for palliative home care service, and help to identify specific interventions.